Exploring the Connections between Employment and the Housing Crisis in Cambridge Bay, Nunavut - Song, Gloria (Études Inuit Studies, 2025)
This article examines the role of housing with respect to goals of increasing Inuit employment. This is part of a larger project that used institutional ethnography to interview service providers and community members in Cambridge Bay, Nunavut to understand how their experiences of the housing crisis are coordinated by the institutional features of bureaucratic systems in Nunavut. The research confirms significant correlations between housing and employment. Local Inuit skilled workers must consider moving out of Cambridge Bay due to the lack of affordable housing. The housing crisis is also affected by the employment context, as local labor shortages contribute to challenges in building and maintaining homes in the community. Staff housing is one solution used by employers to incentivize the hiring and retaining of local skilled workers in Nunavut and support Inuit participation in the labor force. However, other solutions are needed, as workers living in staff housing risk losing their home if their employment is terminated, leaving them in a legally precarious position. To sustainably support Inuit employment, the housing crisis must be dealt with in a holistic manner, addressing all types of housing.